2018
DOI: 10.1093/cvr/cvy169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coronary revascularization on global coronary flow reserve in stable coronary artery disease

Abstract: Coronary revascularisation ameliorated reduced CFR in patients with obstructive CAD. The degree of improvement in angiographic CAD burden by revascularisation was correlated with magnitude of improvement in CFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…Additionally, our results indicated that FFR‐guided revascularization decision‐making could not improve g‐CFR and HCSF in approximately 50% and 30% patients, suggesting that considering factors in addition to FFR could optimize the identification of patients in whom coronary flow improvement can be expected with respect to the concordant improvement in HCSF and g‐CFR (Figure 3 and Table 3). These results are in line with the recent study using PET 3 and suggest the potential ability of PC‐CMR‐derived factors to predict coronary flow improvement in addition to FFR. The existence and extent of ischemia have been proposed as an essential factor in stable CAD and a therapeutic target; however, no previous studies have documented a reduced risk of death or MI in relation to absolute coronary flow improvement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, our results indicated that FFR‐guided revascularization decision‐making could not improve g‐CFR and HCSF in approximately 50% and 30% patients, suggesting that considering factors in addition to FFR could optimize the identification of patients in whom coronary flow improvement can be expected with respect to the concordant improvement in HCSF and g‐CFR (Figure 3 and Table 3). These results are in line with the recent study using PET 3 and suggest the potential ability of PC‐CMR‐derived factors to predict coronary flow improvement in addition to FFR. The existence and extent of ischemia have been proposed as an essential factor in stable CAD and a therapeutic target; however, no previous studies have documented a reduced risk of death or MI in relation to absolute coronary flow improvement.…”
Section: Discussionsupporting
confidence: 90%
“…In uncomplicated PCI, post‐PCI hyperemic coronary flow, post‐PCI global coronary flow reserve (g‐CFR), and post‐PCI FFR are expected to improve given less effect from epicardial stenosis, although randomized trials have failed to show a reduced risk of myocardial infarction (MI) and death after PCI in comparison with that after guideline‐directed medical therapy (GDMT) in patients with stable coronary artery disease (CAD). In a previous study, revascularization improved the regional coronary flow reserve (CFR) and stress myocardial blood flow using positron emission tomography (PET) 3 . The degree of improvement was correlated with the degree of reduction of epicardial atherosclerotic burden.…”
Section: Introductionmentioning
confidence: 87%
“…The primary outcome of this prospective study was to assess the effects of coronary revascularization on CFR, and the findings were recently published. [6] Blood Chemical Analysis Venous blood samples were obtained at the same time as the PET scans. They were centrifuged at 4°C at 2,500 rpm for 15 min, and their supernatant was stored at −70°C.…”
Section: Study Populationmentioning
confidence: 99%
“…Coronary revascularization can relieve the flow-limiting stenosis, but cannot ameliorate CMD. [6] The optimal medical therapies for CAD, such as exercise [7],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation